Effect of a hydrogen peroxide bleaching agent with calcium and phosphorus-containing salts on enamel surface hardness and roughness - Andrade, Adrielle Cm [UNESP]; Tenuta, Livia Ma; Borges, Allessandra B. [UNESP]; Torres, Carlos Rg [UNESP] (My University, 2021)
PURPOSE: To evaluate whether adding calcium and phosphorus-containing salts to 35% hydrogen peroxide at saturation concentrations with respect to hydroxyapatite would reduce its deleterious effects on bleached enamel or affect bleaching efficacy. METHODS: The saturation concentrations of elemental calcium and phosphorus in a 35% hydrogen peroxide solution were determined after equilibration with powdered enamel. The solubility limit of the salts in 35% hydrogen peroxide was then experimentally determined. Polished bovine enamel-dentin specimens (n=120) with known baseline enamel Knoop microhardness (KHN), surface roughness (Ra), and color were bleached with hydrogen peroxide containing different concentrations of calcium and phosphorus-containing salts as follows: Negative Control - water without any addition; Positive Control - 35% hydrogen peroxide without any addition; 50% of Ca and P - hydrogen peroxide with calcium and phosphorus-containing salt additions of 50% of the saturation concentration; 100% of Ca and P - hydrogen peroxide with calcium and phosphorus-containing salt additions of 100% of the saturation concentration; Ca limit - hydrogen peroxide with addition of calcium-containing salt at the solubility limit, and P limit - hydrogen peroxide with addition of phosphate-containing salt at the solubility limit. The prepared bleaching solutions were applied on the surface of the specimens for 60 minutes. The microhardness and surface roughness were measured immediately after bleaching, and the color change (ΔE*00) was evaluated after 7 days. RESULTS: One-way ANOVA showed significant differences among the groups for all evaluations (P< 0.05). The groups saturated with elemental calcium and/or phosphorus with respect to hydroxyapatite did not show significant changes in microhardness and roughness in relation to the negative control, while the positive control without mineral supplementation and the 50% saturated group showed reduced microhardness and increased roughness. The addition of calcium and/or phosphorus-containing salts in sufficient concentrations to create a saturated hydrogen peroxide solution with respect to hydroxyapatite was able to completely prevent surface changes without affecting the bleaching effect. CLINICAL SIGNIFICANCE: The addition of ions at saturation concentrations or higher with respect to hydroxyapatite can prevent enamel demineralization without compromising the efficacy of bleaching gels.